The night is defying [large type] - Peñaranda, Chloe C. (Peñaranda, Chloe C. Nytefall trilogy, 2025)
"Shaken from the aftermath of the Libertatem, the newly found star-maiden Astraea is determined to keep her freedom, even at the cost of betraying her heart. But time is running out to recover her memories with the hope it will unveil her killer. Embarking on a journey to discover her past, Astraea's awakening power spins the hourglass on a history threatening to repeat itself. While Nyte tries to regain control of the vampires hungry for bloodshed, a sinister plan by his brother to overthrow him sparks a dangerous feud. But are they willing to wear the blood of their kin to see it through?"--